EL RETABLO MAYOR DE LA PARROQUIA DE LA ASUNCIÓN DE HELLÍN - De La Peña Velasco, Concepción; Máximo García, Enrique (Imafronte, 2008)
We have studied the disoppeared main altarpiece of the parish of Hellin though an old photograph and some ancient document regarding the sculpture and gilding, that provide new details on Juan Sánchez Cordobés and reveal the names of otlier artists such as Bartolomé Saloni, a XVIIIh century constructor and sculpture, as well as those of other gilders.